2021
DOI: 10.1093/alcalc/agab057
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Anticonvulsants for the Inpatient Treatment of Alcohol Withdrawal Syndrome: A Systematic Review and Meta-analysis

Abstract: Aim To examine the efficacy and safety of antiepileptic drugs (AED) for the inpatient treatment of patients with moderate to severe alcohol withdrawal syndrome (AWS). Methods We searched in databases and gray literature to include randomized controlled clinical trials in adults that compare the use of AED versus placebo or any other medication. Studies that did not specify severity or were performed on an outpatient basis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…A recent systematic review and meta-analysis evaluated 26 randomized controlled trials comparing various AEDs to benzodiazepines or placebo. 58 The review found no difference in rate of AWS, seizure, or DTs. There was a non-statistically significant increase in the rate of mild or moderate adverse effects (dizziness, ataxia, nausea, and vomiting) with carbamazepine and valproic acid use.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…A recent systematic review and meta-analysis evaluated 26 randomized controlled trials comparing various AEDs to benzodiazepines or placebo. 58 The review found no difference in rate of AWS, seizure, or DTs. There was a non-statistically significant increase in the rate of mild or moderate adverse effects (dizziness, ataxia, nausea, and vomiting) with carbamazepine and valproic acid use.…”
Section: Discussionmentioning
confidence: 92%
“…Although the overall quality of evidence was low as analyzed by the cited systematic review and meta-analysis, the use of AEDs is not recommended for prophylaxis or treatment of patients with AWS. 58 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, repeated alcohol withdrawal episodes increase neuronal sensitivity and excitability, a phenomenon called "kindling" which leads to more severe and lasting withdrawal symptoms [55,56]. The reduction of kindling can alleviate symptoms, complications, and sequelae related to alcohol withdrawal syndrome (AWS) [55,57,58]. This phenomenon is not unique to humans and has been observed in relevant studies on other animals.…”
Section: Medicine Advances -333mentioning
confidence: 99%